UTILIZING SPICE SIMULATION TO ADVANCE CIRCUIT DESIGN PROFICIENCY AMONG ELECTRICAL ENGINEERING STUDENTS IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigates the efficacy of SPICE (Simulation Program with Integrated Circuit Emphasis) simulation in enhancing circuit design proficiency among electrical engineering students in Cross River State, Nigeria. With the increasing complexity of modern electronics, proficiency in circuit design is critical for engineering graduates. However, traditional teaching methods often lack practical, hands-on simulation tools like SPICE, which can bridge theoretical knowledge and real-world application. Using a primary data collection method, this research involved 120 students from two institutions, the University of Calabar and the Cross River University of Technology, divided into experimental (SPICE-integrated) and control (traditional) groups. Pre- and post-intervention assessments measured circuit design skills, focusing on accuracy, speed, and problem-solving ability. Results revealed that the experimental group exhibited a statistically significant improvement (p < 0.05), with a mean score increase of 15.6 points compared to 4.2 in the control group. Qualitative feedback highlighted SPICE’s role in enhancing understanding of circuit behavior and reducing design errors. The study aligns with global trends in engineering education, emphasizing simulation tools’ transformative potential. Challenges such as limited computer access and software familiarity were noted, suggesting the need for infrastructural investment and training. This research contributes to the discourse on technology-enhanced learning in developing contexts, recommending the integration of SPICE into electrical engineering curricula in Cross River State to prepare students for industry demands. Future studies should explore long-term impacts and scalability across Nigeria.